Upaya Peningkatan Hasil Belajar Aqidah Akhlak melalui Media Interaktif pada Siswa MA Intisyarul Ulum Kota Probolinggo - Adiba Maulidiyah; Moch.Salman Alfarizi; Devy Habibi Muhammad (ISLAMIKA, 2022)
The subject of aqidah morals is called part of the branch of Islamic Religious Sciences which is so important and has a function in the life of this globalization era. Teaching and learning activities, especially the Aqidah Akhlak subject, are the main milestones in the formation of character for students in their daily life spiritually and morally. The purpose of this study is to improve student learning outcomes, especially in the chapter on avoiding despicable ahlaq. This type of research is classroom action research (CAR). The subjects were students of class X, totaling 36 students. Data collection techniques used include observation, interviews, documentation, observations and tests. The data analysis used is quantitative and qualitative. The results showed an increase in the percentage of students' understanding of the pre-cycle, cycle I and cycle II. In the pre-cycle, the percentage value was only 36%, the first cycle was only 44% and the second cycle rose to 89%. students can be said to be complete if their learning outcomes can exceed the predetermined KKM of 75. The increase in learning outcomes is because researchers make improvements to learning in the aspect of learning media. In this case, researchers use interactive media that is presented using Auto Play Media. Thus it can be concluded that the use of learning models with interactive media presented using Auto Play Media can improve learning outcomes of Aqidah Ahlaq material for students at MA Intisyarul Ulum Probolinggo City.